2020
DOI: 10.1080/20442041.2019.1700749
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotoxin occurrence in large rivers of the United States

Abstract: Cyanotoxins occur in rivers worldwide but are understudied in lotic ecosystems relative to lakes and reservoirs. We sampled 11 large river sites located throughout the United States during June-September 2017 to determine the occurrence of cyanobacteria with known cyanotoxinproducing strains, cyanotoxin synthetase genes, and cyanotoxins. Chlorophyll a concentrations ranged from oligotrophic to eutrophic (0.5-64.4 µg L − 1 ). Cyanobacteria were present in the algal communities of all rivers (82% of samples, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 35 publications
1
28
1
Order By: Relevance
“…While existing data show cyanotoxins present in water sources in the US and worldwide [20,[123][124][125], treatment plants and private water sources may not be affected uniformly. Surface water accounts for nearly three-quarters of annual water withdrawals in the US but about 50% of the public water supply that reaches about 141 million people or 43.5% of the US population [126].…”
Section: Future Outlookmentioning
confidence: 95%
See 1 more Smart Citation
“…While existing data show cyanotoxins present in water sources in the US and worldwide [20,[123][124][125], treatment plants and private water sources may not be affected uniformly. Surface water accounts for nearly three-quarters of annual water withdrawals in the US but about 50% of the public water supply that reaches about 141 million people or 43.5% of the US population [126].…”
Section: Future Outlookmentioning
confidence: 95%
“…Finally, negative human health impacts are illustrated by Figure 1. Unites States Geological 2017 Survey (USGS) of 11 major coastal and inland rivers of the US for the detection of four cyanotoxins and their genes: mcyE (microcystins), anaC (anatoxins), sxtA (saxitoxins), and cyrA (cylindrospermopsin) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Intensification of low-flow conditions can impact fish species and communities at local and regional scales through increased mortality and disruption of reproduction, recruitment, and dispersal [2,7,60]. Nuisance and/or harmful algal blooms (HABs) and associated decreases in dissolved oxygen often occur during low flows, and cyanobacteria HABs and toxicity in lotic ecosystems are an increasing management concern in some regions [61,62]. Use of percentage-of-flow and presumptive standards are increasingly popular among water-management agencies within the US and elsewhere [30,57,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of research on this topic may be due to the greater likelihood of observing cyanobacterial blooms in lentic environments than in their lotic counterparts or because riverine conditions (including high turbulence, low light, short residence times, and cooler temperatures) are not typically associated with high algal growth rates (Paerl and Otten, 2013). Nevertheless, a recent study of 11 major rivers in the US showed that cyanobacteria was present in all rivers and comprised up to 52% of the community composition (Graham et al, 2020). The present study shows that rivers may play a critical role in the promotion of newly occurring cyanobacterial blooms in Lake Superior.…”
Section: Discussionmentioning
confidence: 99%